The Effect of Compensation, Work Motivation, and Work Discipline on Employee Performance - St. Nur Wahidah Thachyuddin; Bahar Sinring; Amir Mahmud (Golden Ratio of Mapping Idea and Literature Format, 2025)
This study aims to examine the effect of compensation, work motivation, and work discipline on employee performance at PT. Yong Xing Abadi Jaya, Makassar City. The data for this study were obtained from the employees of PT. Yong Xing Abadi Jaya in Makassar City in 2025, specifically those employees willing to participate as respondents. This study employed primary data collected through direct field research, where questionnaires/statements were distributed to respondents. The sample selection utilized a census method due to the small sample size, ensuring that the sample represents the entire population of 60 employees. The data analysis was conducted using descriptive statistical analysis and SPSS 26.0. The results of the study indicate that compensation, work motivation, and work discipline have a positive and significant effect on employee performance at PT. Yong Xing Abadi Jaya. Appropriate compensation based on performance motivates employees to perform better, while high work motivation serves as an important driving force for achieving optimal results. Good work discipline creates a well-ordered and efficient work environment, contributing to improved performance both individually and as a team. Therefore, the company needs to focus on providing appropriate compensation, enhancing employee motivation, and maintaining a disciplined culture to support optimal performance.